Targeting Prostate Cancer with Rambutan Peel-Derived Compounds via Network Pharmacology - Utami, Wulandari Putri; Tallei, Trina Ekawati; Turalaki, Grace Lendawati Amelia; Tendean, Lydia Estelina Naomi; Kaseke, Martha Marie; Purwanto, Diana Shintawati (Malacca Pharmaceutics, 2025)
Prostate cancer is a prevalent malignancy in men, originating in the prostate gland and often driven by genetic alterations and hormonal dysregulation. Rambutan (Nephelium lappaceum L.) peel, a byproduct of fruit consumption, has demonstrated potential anticancer activity. This study employed a network pharmacology-based in silico approach to evaluate the therapeutic potential of rambutan peel extract in prostate cancer treatment. Bioactive compounds were identified through database searches, and their biological activities were predicted using PASS Online. Pharmacokinetic and toxicity profiles were assessed using ADMETLab 3.0 and Protox 3.0 to evaluate safety and drug-like properties. Potential target proteins were identified via SwissTargetPrediction and GeneCards, while protein-protein interaction networks were constructed using STRING. The pharmacological networks were visualized using Cytoscape to elucidate molecular mechanisms of action. The analysis identified 28 bioactive compounds in rambutan peel extract, with 11 demonstrating activity against prostate cancer (Pa > 0.5). These compounds were deemed safe based on Lipinski's Rule of Five (Ro5) and categorized within toxicity classes V and VI. Rambutan peel extract was found to target 501 proteins associated with prostate cancer, including key pathways involved in resistance to EGFR tyrosine kinase inhibitors. Network pharmacology analysis highlighted several key target genes, including SRC, GNAI1, PIK3CA, PIK3CD, MAPK1, MAPK3, AKT1, GNAI3, PRKCA, and HSP90AA1. Among these, SRC exhibited the highest centrality score, underscoring its pivotal role in disrupting tumorigenic and metastatic signaling pathways, suppressing cancer cell proliferation, and enhancing therapeutic responses. These findings suggest that rambutan peel extract holds promise as a natural therapeutic agent for prostate cancer, warranting further experimental and clinical validation.